Estudio longitudinal de los parámetros de calidad de vida en pacientes oncológicos - Padierna, Celina; Fernández, Concepción; Amigo, Isaac; Gracia, José Manuel; Fernández, Roberto; Peláez, Ignacio; Pérez, Marino (Psicooncología, 2004)
Purpose. To realize a longitudinal quality of life evaluation in a representative sample of cancer patients by means of different instruments (semi-structured interviews, standarized questionnaires (Karnofsky Performance Status, HAD and QL-CA-AFex), registers) and by different observers (patients and doctors). Method. 101 new patients in the cancer department of Cabueñes hospital were selected consecutively. Quality of life was assessed at seven time points: baseline, start of treatment, second cycle of treatment, third cycle of treatment, end of treatment, three and six months after treatment. Results. Descriptive data and variations in quality of life over time are showed. Conclusions. Comparison of quality of life reports informed by different methods and different observers showed some discrepancies. Results showed that there are relevant parameters in each moment of illness that contributes especially to patients’ quality of life.